Alcohol Use Disorder, Neurodegeneration, Alzheimer’s and Parkinson’s Disease: Interplay Between Oxidative Stress, Neuroimmune Response and Excitotoxicity - Kamal, Haziq; Tan, Geok Chin; Ibrahim, Siti Fatimah; Shaikh, Mohd. Farooq; Mohamed, Isa Naina; Mohamed, Rashidi M. Pakri; Hamid, Adila A.; Ugusman, Azizah; Kumar, Jaya (Frontiers in Cellular Neuroscience, 2020)
Alcohol Use Disorder (AUD) has been associated with neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. Prolonged excessive alcohol intake contributes to increased production of reactive oxygen species that trigger neuroimmune response and cellular apoptosis and necrosis via lipid peroxidation, mitochondrial, protein, or DNA damage. Long term binge alcohol consumption also upregulates glutamate receptors, glucocorticoids and reduces the reuptake of glutamate in the central nervous system, resulting in glutamate excitotoxicity, and eventually mitochondrial injury and cell death. In this review, we delineate the following principles in alcohol-induced neurodegeneration: 1) alcohol-induced oxidative stress, 2) neuroimmune response towards increased oxidants and lipopolysaccharide, 3) glutamate excitotoxicity and cell injury, and 4) interplay between oxidative stress, neuroimmune response, and excitotoxicity leading to neurodegeneration and 5) potential chronic alcohol intake-induced development of neurodegenerative diseases, including Alzheimer’s and Parkinson’s disease.